Incidence of Hypertension of 30-50 Years Old in the Salatiga City Health Center - sinta septiyawati, Gabrial; Hary Cahyati, Widya; Raffy Rustiana, Eunike Raffy Rustiana (Public Health Perspective Journal, 2021)
The prevalence of hypertension in Indonesia based on measurement of blood pressure at age Ã¢â€°Â¥18 years was 7.5% in 2007, an increase in 2013 by 9.5% and an increase again in 2016 by 30,9%. The purpose of this study was to analyze the factors that influence the incidence of hypertension at the age of 30-50 years at the Salatiga City Health Center. The study design in this research is case control. The population in this study were people aged 30-50 years in the working area of Puskesmas Kota Salatiga, namely Puskesmas Cebongan, Puskesmas Kalicacing and Puskesmas Sidorejo Lor. The sample consisted of 35 cases group, 35 control group as well. The sampling method used purposive sampling technique. The instrument used was a questionnaire containing questions on gender, exercise habits, stress levels / DASS questionnaires, BMI, genetic history and a tool to measure the respondent's blood pressure, namely the mercury spignomanometer. Data analysis used chi-square and logistic regression. There was no effect between sex on the incidence of hypertension (p = 0.633; OR = 0.709). There was an influence between genetic history (p = 0.017; OR = 11.769), smoking status (p = 0.036; OR = 4.889), obesity (p = 0.049; OR = 5.717), alcohol consumption (p = 0.025; OR = 0.453), salt consumption (p = 0.017; OR = 4.500), stress levels (p = 0.026; OR = 4.580), exercise habits (p = 0.020; OR = 0.246) the incidence of hypertension. The factors that most influenced the incidence of hypertension were exercise habits (p = 0.018; OR = 5.006), stress levels (p = 0.053; OR = 0.251), and salt consumption (p = 0.035; OR = 0.239).Ã‚Â  Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â